ANALYSIS OF GOVERNOR'S INSTRUCTION DIY NO: K.898/I/A/75 ON LAND OWNERSHIP IN YOGYAKARTA BY INDONESIAN CITIZENS OF CHINESE DESCENT FROM THE PERSPECTIVE OF JUSTICE. - Piong Khoy Fung; Rosalina Indah Sari; Anyelir Pupsa Kumala (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2023)
The Governor's Instruction in Yogyakarta that prohibits land ownership for the Chinese community has roots in a long history of resentment that predates independence. In this context, the issuance of the Letter of Instruction by the Head of the Special Region of Yogyakarta in 1975, signed by Paku Alam VIII, becomes relevant. The instruction orders the denial of land ownership to non-indigenous citizens and is linked to Law No. 13 of 2012 on the special status of the Yogyakarta special region, which legitimizes the instruction in the field of land through Article 1 and Article 7. While general land laws apply there, the policy of standardizing land ownership in the governor's instruction states that the Chinese community, referred to as non-indigenous in the instruction, are not entitled to own land in Yogyakarta. However, since the amendment of the 1945 Constitution in 2002, there is no longer any distinction between indigenous and non-indigenous citizens. Therefore, the relevance of the instruction to current regulations is inconsistent with the principles of justice and equal rights as Indonesian citizens. The instruction clearly creates discrimination that undermines justice for Indonesian citizens of Chinese descent and contradicts the Indonesian constitution, which guarantees equal rights and justice for all citizens. Referring to the post-amendment 1945 Constitution, Article 26, paragraph (1) states,